A study on the potential role of autophagy‐related protein 10 as a biomarker for ulcerative colitis. Issue 7 (27th April 2021) - Abbasi Teshnizi, Fatemeh; Kazemipour, Nasrin; Nazifi, Saeed; Bagheri Lankarani, Kamran; Sepehrimanesh, Masood; Razeghian Jahromi, Iman
Abstract: Purpose: Ulcerative colitis (UC) is a lifelong disease with unclear etiology and increasing prevalence worldwide. Autophagy has been reported to play roles in the pathogenesis and progression of UC. Here, we aimed to analyze the expression of autophagy related protein 10 (ATG10) and its regulator, micro‐RNA (miR) 519a, in UC patients. Methods: The level of ATG10 in the serum, stool, and colon biopsies from 15 UC patients and 30 non‐UC healthy individuals (HC) group was measured by ELISA. Also, the blood level of miR‐519a was investigated by quantitative real‐time PCR. Results: We found 13.63 ng/ml versus 0.99 ng/ml, 11.01 ng/ml versus 1.11 ng/ml and 6.41 ng/ml versus 3.21 ng/ml of ATG10 in the stool, colon tissue, and serum of UC and HC, respectively. There was no significant difference in the expression of miR‐519a in the blood samples of UC and HC. Conclusions: ATG10 might be a potential non‐invasive diagnostic biomarker for UC.